106k views
4 votes
Y= 1/3x+3
Y=2x-2
How can I solve of systems of equation substitution.?​

User Bilak
by
5.5k points

1 Answer

4 votes

Answer:

x=3, Y= 4

Explanation:

① Label the 2 equations

Y= ⅓x +3 -----(1)

Y= 2x -2 -----(2)

② Since both equations are Y= ____, substitute one equation into the other so that we are left with x terms and constant only.

subst. (1) into (2):

⅓x +3= 2x -2

③ Bring x terms to one side and constants to the other.

2x -⅓x= 3 +2

simplify:


(5)/(3) x = 5


x = 5 / (5)/(3) \\ x = 5 * (3)/(5) \\ x = 3

④ Solve for y.

Subst. x=3 into (2):

Y= 2(3) -2

Y= 6 -2

Y= 4

User LeftOnTheMoon
by
4.8k points